ARCHAEOLOGY WITH THE CITY - Tessaro, Piero Alessandro Bohn (2022)
This paper reflex on the development of the concept of an Archaeology with the City, expanding the concepts of Archaeology in the City, of the City and for the City. Such new concept was developed within the scope Urban archeology projects in the City of São Paulo, in dialaogue with proposals from Sociomuseology, since most researches aimed at musealization of Archeology. Despite archaeology with the city being born from encounters between Urban archaeology and Sociomuseology, this path also brought up closer dialogues with Public and Collaborative archaeology, safeguarding the specificities of considering the city an Archaeological Site, as usual among archaeologists working with urban contexts. Thus, new challenges are posed to the practice of Archaeology with the City.